Recession and its aftermath: The Cape Colony in the eighteen eighties - Mabin, Alan (My University, 1984)
The urban and industrial transformation of South Africa is commonly considered to have begun with the discoveries of diamonds in 1867 and of gold in 1886. Among the components of that transformation were the reorientations on two occasions of the economies of the coastal colonies of the Cape and Natal towards 'emerging economic centres of gravity1 at Kimberley and Johannesburg. The diversion to the interior of capital investment in the late nineteenth century has been paralleled by the focus of much late twentieth century historiography, which has - with exceptions - been concerned more with events after than before the opening of the Witwatersrand gold fields, and which has seldom explored the economic conditions prevailing in the coastal colonies prior to that moment. It seems to be taken for granted that the mineral 'discoveries' should have been followed by so unusual a reorientation of the pre-existing geography: not once,' but twice: first to the diamond fields, then to the Transvaal. The geological occurrence or geographical location of minerals substitutes for explanation of movements of money, people and materials. Yet as Atmore and Marks hinted, following a theme suggested by Blainey, minerals were discovered 'by no means entirely accidentally' at particular moments in the sixties and the eighties.The timing and the geography of the economic expansions of which mineral discoveries and evelopment formed a part are subjects which both history and historical geography have left uncharted. This paper is concerned with the economic conditions prevailing in the Cape Colony in the early eighties, immediately prior to the opening of the Witwatersrand mines. Its first section charts the course of recession from 1881 to 1886. The remainder of the paper considers the consequences of the depression in the Cape Colony and its association with certain other factors in South African development at the time. Its last two sections analyse the various forces, arising before and during the recession, which both encouraged and opposed northward expansion from the Cape Colony.
African Studies Seminar series. Paper presented 27 August 1984
Keywords: Eastern Cape (South Africa). Economic conditions; Cape of Good Hope (South Africa). Economic conditions